Поздовжньо-поперечна течія стискаючої рідини, залежної від швидкості зрушення і тиску вздовж щілинного каналу шнекової машини. Частина 1 - Товажнянський, Леонід Леонідович; Білецький, Е. В.; Толчинський, Юрій Аврамович (Національний університет харчових технологій, 2012)
Вивчена проблема математичного моделювання квазі-в'язкого потоку рідини в щілинних каналах шнекових машин. Наводиться рівняння для визначення витрат рідини у каналі. Отримані дані дозволяють моделювати інші в'язкопластичні рідини.

The article studies the problem of mathematical modelling of quasi-viscous liquid flow in screw machine slot channels. It also proposes the algorithm which allows using simple algebraic reductions instead of solving complex differential equations. The equations obtained permit to generalize classical results for non-linear liquid flow with viscosity depending on the shear rate with parameters randomly dependent on pressure. The relationship between three-dimensional resulting tasks and one-dimensional ones are shown to be concentrated in renormalized viscosity function coefficients. The data obtained allow to model different types of viscoelastic flows.
Transverse and longitudinal flow of compressible fluid with viscosity depending on the shear rate and pressure along the slot channel of the screw machine. Part 1
Keywords: в'язкопластична рідина; течія Куетта; модель реології; щілинний канал; швидкість зрушення; viscoplastic fluid; Couette flow; shear rate; rheological model; slotted channel; screw machine